Copihues entre orquídeas: mujeres chilenas exiliadas en Costa Rica (1973-2003) - Gutiérrez Rojas, Marisol (2016)
This article deals with a qualitative approach to a living experience of Chilean women in Costa Rica. They were successful not only in there daily activities but also in the way they succeed professionally in this costarrican experience.